Transnational Purepecha Diaspora in the United States - Leco Tomás, Casimiro (Acta Universitaria, 2013)
This article analyses the creation of a new diaspora, that of the Purepecha people, native from an indigenous region in the state of Michoacan, Mexico, which has acquired an important presence in the United States due to the number of its inhabitants living in that country. The geographical position of the two countries has promoted close communications and continuous movements of people between regions, giving way to the creation of transnational Purepecha communities that possess unique characteristics, which give meaning to their ethnic identity and strengthen the notion of diaspora
Keywords: Array; Array; Array; Array; Array